Human Resource Readiness in Facing the Implementation of Digital Technology: A Study of Training Needs and Competency Development - Satiti, Rezky Purna (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
The rapid digital transformation requires human resources (HR) to be able to adapt to various new technologies in the work environment. This research aims to analyze the level of readiness of human resources in facing the implementation of digital technology, identify the digital competencies needed, and formulate relevant training strategies based on actual needs. The research method used was descriptive quantitative with a survey approach of 120 respondents from the service and public administration sectors. The results show that HR readiness levels vary, with younger generations and operational job positions showing higher readiness than senior generation and top-level management. The most needed digital competencies include basic digital literacy, data analysis skills, work software utilization, cybersecurity, and digital communication. The main implication of these findings is the need for initial competency mapping and the implementation of need-based training to effectively address the challenges of digital transformation. The study also identified implementation barriers, such as budget constraints, resistance to change, and lack of top management support. These findings make an important contribution to the formulation of adaptive and sustainable HR development strategies in the digital era